Peningkatan Profesionalisme Guru Akuntansi Pada Kompetensi Dasar Memahami Akuntansi Lembaga - Eka Rahmawati; Amir Mahmud; Nurdian Susilowati (Unri Conference Series: Community Engagement, 2021)
One of the new essential competencies in the revised 2013 Curriculum is understanding village financial management. Basic competence to understand village financial management is urgent to learn because of new knowledge in accounting. Therefore, teachers must move to learn from various sources, including academics. This community service activity aims to increase understanding of the scope of village financial management and knowledge of income, expenditure, and village financing activities. Furthermore, a comprehensive evaluation of the training is carried out to compile reports on village assets. The training activity was attended by 80 vocational high schools (SMK) accounting teachers in Pemalang using virtual zoom meetings. The result is that teachers can understand the scope of village financial management and its functions. The concepts of income, expenditure and financing can be carefully understood and practised how to apply them. The accounting basis used is the cash basis, so that so far, the financial records are still straightforward